„Mnie wiara jest widzeniem i za wszystkie mi z rozumu i zmysłów wywody stoi”. Rok Święty w świetle "Kazania na Miłościwe Lato abo Jubileusz" Piotra Skargi - Wichowa, Maria (Tematy i Konteksty, 2014)
Holy Years had a great significance for the spiritual culture in 16th/17th century Poland. Participation in the celebration of the jubilee allowed the renaissance of faithful and required fulfilling multiple conditions as defined by the Church. For the circumstances of Holy Years, there were special sermons prepared. One of them was written by Piotr Skarga. The text is designed as a role model among sermons, intended for frequent use by preachers. Skarga presents himself in this sermon as a "specialist", excellent subject matter expert, well acquainted with theology and the origins of the described events. In his persuasion and argumentation, Skarga tries to adjust the rhetorical means to the intellectual and spiritual predispositions of the recipients of the sermon. For example, he presents to the faithful abstract concepts through the phenomena known to them from their everyday life, he uses simple explanations of difficult theological questions. This sermon acts as a spiritual guide, a means to shape public opinion, an efficient tool of religious teaching and achieving the objectives of the Jesuits. The work has a utilitarian character.